Greater Great Lakes Regional Strategy for Demobilization and Reintegration - World Bank (Washington, DC, 2013)
This document first outlines a comprehensive strategy for disarmament, demobilization and reintegration (DDR) activities in the greater Great Lakes region of central Africa. The purpose of this strategy is to enhance the prospects for stabilization and recovery in the region. The DDR of the ex-combatants is necessary to establishing peace and restoring security, which are in turn pre-conditions for sustainable growth and poverty reduction. A multi-country approach will enhance effectiveness of the international response, provide greater coherence among DDR activities, facilitate positive feedback relationships among DDR activities in the region, provide similar incentives for all parties to the conflict to pursue peaceful strategies, address the regional externalities associated with some individual programs, enhance transparency of closely related DDR activities, and facilitate knowledge-sharing and training across DDR implementers. A regional strategy also serves as a confidence-building measure. The strategy, if successfully implemented, will have a significant impact on reducing poverty by helping to consolidate peace, building confidence among governments in the region, helping to free up national resources for investment, attracting foreign capital, investing in the human capital of ex-combatants, and enhancing capacities for development at the community level.